Answer: of ok
Step-by-step explanation:
This
Answer:
0
Step-by-step explanation:
g[f(x)] = x^2 - 3
= 3x^2
if gf(0) = 3(0)^2
= 0
Answer: 66s + 180
How:
17 s ^ { 1 } 2 + 32 s + 180
Calculate s to the power of 1 and get s.
17s\times 2+32s+180
Multiply 17 and 2 to get 34.
34s+32s+180
Combine 34s and 32s to get 66s.
Final answer should be 66s + 180
Answer:
I think it is ikinetic because it gains speed as it gets closer to the ground.
These require you solve for y. Do that by subtracting the x-term, then dividing by the y-coefficient.
5. 3y = 7x -9
y = (7/3)x -3
6. 6y = -2x -3
y = (-2/6)x -3/6
y = (-1/3)x -1/2
7. 8y = 2x + 12
y = (1/4)x +3/2